Authorea
DOI: 10.22541/au.158456440.01903363
|View full text |Cite
|
Sign up to set email alerts
|

A layover in Europe: reconstructing the invasion route of asexual lineages of a New Zealand snail to North America

Abstract: Non-native species are threatening ecosystems and biodiversity worldwide. High genetic variation is thought to be a critical factor for invasion success. The global invasion of a few clonal lineages of the gastropod Potamopyrgus antipodarum is thus both puzzling and has the potential to help illuminate why some invasions succeed while others fail. Here, we used SNP markers and a geographically broad sampling scheme (N = 1617) including native New Zealand populations and invasive North American and European pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…In other systems, it has been shown that invaders have lower microbial diversity and/or a subset of microbes relative to that present in native populations (Minard et al, 2015;Zepeda-Paulo et al, 2018). Invasive P. antipodarum populations feature low genotypic diversity relative to the native range (Donne et al, 2020;Dybdahl & Drown, 2011;Verhaegen et al, 2018) and mitochondrial haplotypes of invaders represent genetic subsets of native mitochondrial haplotype diversity (Städler et al, 2005). However, this genetic subsampling in invasive P. antipodarum populations is not reflected in their microbiota microbiome down to specialized taxa (Foster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In other systems, it has been shown that invaders have lower microbial diversity and/or a subset of microbes relative to that present in native populations (Minard et al, 2015;Zepeda-Paulo et al, 2018). Invasive P. antipodarum populations feature low genotypic diversity relative to the native range (Donne et al, 2020;Dybdahl & Drown, 2011;Verhaegen et al, 2018) and mitochondrial haplotypes of invaders represent genetic subsets of native mitochondrial haplotype diversity (Städler et al, 2005). However, this genetic subsampling in invasive P. antipodarum populations is not reflected in their microbiota microbiome down to specialized taxa (Foster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In other systems, it has been shown that invaders have lower microbial diversity and/or a subset of microbes relative to that present in native populations (15,16). Invasive P. antipodarum populations feature low genotypic diversity relative to the native range (31,54,55) and mitochondrial haplotypes of invaders represent genetic subsets of native mitochondrial haplotype diversity (17). However, this genetic subsampling in invasive P. antipodarum populations is not reflected in their microbiota diversity.…”
Section: Discussionmentioning
confidence: 99%